The Spread of Muslim Feminist Ideas in Indonesia: Before and After the Digital Era - Nina Nurmila (Al-Jami'ah: Journal of Islamic Studies, 2021)
Internet has changed the way how knowledge is spread. This paper describes the spread of Muslim feminist ideas in Indonesia. It answers the questions of what constitute feminist ideas, how Muslim feminist ideas spread before and after the Digital Era and what challenges and opportunities provided by the internet that hinder and help the spread of these ideas. Muslim feminism has spread in Indonesia since the early 1990s through the translation of the works of non-Indonesian Muslim feminists such as Fatima Mernissi, Riffat Hassan, Asghar Ali Engineer and Amina Wadud. Since 2010, the increasing use of internet among Indonesians has made the spread of Muslim feminist ideas faster. However, it is challenging that conservative groups also mobilized the internet to oppose Muslim feminist ideas. Another challenge is that not all Indonesian Muslims have easy access to the internet and therefore Indonesian Muslim feminists still have to adopt various offline media such as seminars or radio to spread their ideas. [Internet telah mengubah cara penyebaran pengetahuan. Artikel ini akan menjelaskan penyebaran ide-ide feminis Muslim di Indonesia. Artikel ini akan menjawab pertanyaan tentang apa yang dimaksud dengan ide-ide feminis Muslim, bagaimana ide-ide feminis Muslim tersebar sebelum dan sesudah Era Digital dan tantangan serta kesempatan apa yang diberikan oleh internet yang menghalangi dan membantu penyebaran ide-ide ini. Feminis Muslim telah tersebar di Indonesia sejak awal tahun 1990-an melalui penerjemahan karya-karya Muslim feminis yang bukan dari Indonesia seperti Fatima Mernissi, Riffat Hassan, Asghar Ali Engineer dan Amina Wadud. Sejak tahun 2010, meningkatnya penggunaan internet dikalangan orang Indonesia telah membuat penyebaran ide-ide Muslim feminis lebih cepat. Akan tetapi, terdapat tantangan yaitu bahwa kelompok konservatif pun menggunakan internet untuk menentang ide-ide feminis Muslim. Tantangan lainnya adalah bahwa tidak semua Muslim Indonesia memiliki akses yang mudah terhadap internet, oleh karena itu para feminis Muslim Indonesia masih juga harus menggunakan berbagai media di luar jaringan seperti seminar atau radio untuk menyebarkan ide-ide mereka.]